Analisis Kerusakan Bearing Terhadap Proses Pemasangan dengan menggunakan Metoda Envelope Analysis - Rahman, Taufik; Oscar Haris (Universitas Nusa Putra, 2020)
Bearing Damage Analysis on the Installation Process using the Envelope Analysis Method aims to produce alternative scientific sources and even new scientific sources in the future for both the needs of workshops and the needs of industrial machines that require bearings with a high level of precision, such as boiler machines, chillers etc. After carrying out the envelope analysis method, namely performing a bandpass filter in the range of 500 Hz – 2000 Hz, rectification, and FFT, it can be concluded that the method is not clear enough to show the peaks caused by damage to the rolling bearings. Although there are several peaks that are close to the Bearing Fundamental Frequency, they have relatively smaller amplitudes compared to other peaks under conditions of external track damage, rolling elements, and combination damage. And in the analysis of this installation so that it can be used by industry and people who usually use bearings in installation so that they can find out a good and correct installation so that the bearing does not get damaged quickly, it uses the type of installation and shaft with what tolerances so that the bearing used is durable or resistant. long and also so that the machine used does not have many obstacles in the process of use.